Transparansi Pengelolaan Dana Desa dalam Meningkatkan Kesejahteraan Masyarakat di Nagari Sungai Rimbang Kabupaten Lima Puluh Kota : Penelitian - Octari Putri Aperta; Sinta Westika Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Transparency is one of the principles of good governance, which demands openness to the public regarding the planning, implementation, and accountability of the use of village funds. The purpose of this study is to determine how transparency in village fund management can improve the welfare of the community in Nagari Sungai Rimbang, Lima Puluh Kota Regency. The research method used is a descriptive qualitative approach with data analysis techniques from Miles and Huberman. The results of the study indicate that transparency in village fund management in Nagari Sungai Rimbang, Lima Puluh Kota Regency has not been running optimally. In general, transparency in village fund management in Nagari Sungai Rimbang has followed applicable provisions, but there are shortcomings in direct community involvement in the budget planning and monitoring process so that decisions taken by the village government do not reflect the needs and aspirations of the community. Factors driving transparency are professional human resources, clear rules governing transparency, and healthy environmental competition. And factors inhibiting transparency are the lack of professionalism of human resources and a lack of understanding of the surrounding community. Therefore, it can be concluded that transparency in village fund management in Nagari Sungai Rimbang has not been running optimally and it is hoped that the village government can increase transparency and involve the community in the village fund management process.